The effects of corporate governance on operational risk disclosure in Indonesian Islamic Banking - Lia Yuanisa; Ataina Hudayati; Nawal Kasim (Journal of Contemporary Accounting, 2022)
This study aims to examine the influence of corporate governance on operational risk disclosure in Indonesian Islamic Bank. The corporate governance variables examined in this study are institutional ownership, board of commissioners, audit committee and Sharia Supervisory Board (SSB). The study was conducted on all Sharia banks (13 banks) for the 2014-2018 period using multiple regression method. The results of the study showed that institutional ownership had a significant positive effect on the disclosure of operational risk, and the findings of this study support the hypothesis. However, the board of commissioners, audit committee, and SSB had no effect on the disclosure of operational risk. The results of the study indicated that the hypotheses only partially supported, implying that there are still opportunities to conduct other studies to identify the determinants of operational risk disclosure in Islamic banks. In addition, this study is expected to be able to contribute to measure operational risk disclosures by considering banking regulations in Indonesia.